Distinct Signaling Pathways Regulate TREM2 Phagocytic and NFκB Antagonistic Activities - Yao, Hailan; Coppola, Kyle; Schweig, Jonas Elias; Crawford, Fiona; Mullan, Michael; Paris, Daniel (Frontiers in Cellular Neuroscience, 2019)
Several genetic variants of the Triggering Receptor Expressed on Myeloid Cells-2 (TREM2) have been shown to increase the risk of developing Alzheimer’s disease (AD) supporting a role of microglia and immune cells in the pathobiology of AD. We have developed an ectopic model of TREM2 and DAP12 expression in HEK293 cells to study selectively TREM2 dependent signaling and phagocytic functions and evaluated the effects of some of the TREM2 mutations associated with AD. We show that shedding of the TREM2 N-terminal domain does not affect its anti-inflammatory activity while it completely blocks phagocytosis suggesting that TREM2 anti-inflammatory properties can be mediated by the TREM2 C-terminal fragment while the phagocytic activity requires the full-length receptor. In addition, we confirm in that model that apolipoprotein E (APOE) is a ligand for TREM2 and triggers TREM2 signaling. In particular, we show that APOE4 stimulates spleen tyrosine kinase (SYK) activation more potently than APOE2 in a TREM2 dependent manner. Interestingly, TREM2 appears to antagonize the inflammation induced by phorbol ester but is unable to prevent TNFα induction of NFκB activation suggesting that TREM2 antagonizes inflammatory events triggered downstream of PKC. TREM2 mutations drastically impact TREM2 phagocytosis as well as its anti-inflammatory activity and notably prevent the activation of the PI3K/AKT pathway observed with wild-type TREM2. Overall our data suggest that TREM2 dependent phagocytosis requires an activation of the SYK/PI3K/AKT/PLCγ pathways while its anti-inflammatory activity is independent of SYK, PI3K and PLCγ activities and mediated by a suppression of NFB activation. This model of ectopic TREM2-DAP12 co-expression appears suitable to study TREM2 signaling as several biological functions of TREM2 and TREM2 mutations that have been previously described in myeloid and microglial cells were also replicated in this model.